A NEW ANALYSIS METHOD OF CHILD MORBIDITY BY TERRITORY (ILLUSTRATED BY AN EXAMPLE OF THE OMSK REGION) - Zh. V. Gudinova; E. L. Ovchinnikova; T. A. Neskin; G. N. Zhernakova; E. I. Tol'kova; I. V. Gegechkori ("Paediatrician" Publishers LLC, 2015)
The results of the application of a proprietary methodology for the data analysis «percentile-profile» (through the example of children morbidity in all classes of diseases in the context of municipal districts of the Omsk region). The objective of the technique use is to simplify the perception, to «fold» the complex results of the data set into the drawing, to get information about the complex multicomponent phenomenon. The «percentile-profile» allows to evaluate and compare the data scatter for each class of diseases, peculiarities of children morbidity in each territory, to identify the risk pathology followed by actions focused on its study and prevention. The methodology was approved by the Federal Service of Rospotrebnadzor and tested in the Rospotrebnadzor Administration in the Omsk region. On its basis the socio-sanitary certification of all municipal districts of the region was carried out by 80 statistical indicators of health and environment of the population. The positive results of the implementation of these passports in the practice of municipalities of the Omsk region, in particular in terms of socio-economic development of the region, were obtained.